Pengembangan Model Pembelajaran Project-Based Scaffolding TPACK - Novi Ratna Dewi; Ani Rusilowati; Sigit Saptono; Sri Haryani (Pascasarjana Universitas Negeri Semarang, 2022)
Abstrak. Pembelajaran abad 21 menuntut guru IPA untuk memiliki pengetahuan yang baik dalam mengintegrasikan teknologi ke dalam pengajaran. Penting bagi para guru IPA memiliki pengetahuan tentang teknologi, yang dikenal dengan kerangka TPACK. TPACK memaparkan pengetahuan yang penting bagi guru di era milenial untuk mengintegrasikan teknologi dalam proses pengajarannya. Untuk memastikan peserta didik mampu mengembangkan, mempraktikkan, dan menerapkan keterampilan abad 21, guru IPA harus menguasai TPACK. Tujuan penelitian ini adalah mengembangakan model PBST yang valid dan efektif untuk meningkatkan penguasaan TPACK mahasiswa calon guru. Penelitian ini menggunakan model pengembangan ADDIE. Data validasi ahli dianalisis menggunakan Aiken’s V, data kepraktisan dianalisis secara deskriptif, data penguasaan TPACK dianalisis menggunakan independent t-test. Model PBST hasil pengembangan memiliki sintaks Orientation, Exploration, Workshop, Modelling, Peer Review, Evaluation. Model PBST yang dikembangkan telah teruji valid dan praktis digunakan dalam pembelajaran. Model PBST yang dikembangkan juga terbukti dapat meningkatkan penguasaan TPACK calon guru IPA. Abstract. 21st century learning requires science teachers to have good knowledge in integrating technology into teaching. It is important for science teachers to have knowledge of technology, known as the TPACK framework. TPACK describes the knowledge that is important for teachers in the millennial era to integrate technology in their teaching process. To ensure that students are able to develop, practice, and apply 21st century skills, science teachers must master TPACK. The purpose of this study is to develop a valid and effective PBST model to increase pre-service teachers TPACK mastery. This study uses the ADDIE development model. Expert data validation was analysed using Aiken's V, practicality data was analysed descriptively, mastery of TPACK data was analysed using independent t-test. The results of the development of the PBST Model have the syntax of Orientation, Exploration, Workshop, Modelling, Peer Review, Evaluation. The developed PBST model has been tested and practically used in learning. The developed PBST model is also proven to be able to increase the mastery of TPACK for pre-service science teachers.